Caring load and family caregivers’ burden in China: the mediating effects of social support and social exclusion - Hu, Hongwei; Hu, Xinyi; Xu, Yang (Frontiers in Public Health, 2023)
Objective Caring for older adults with disabilities is a source of stress for family caregivers, and the lack of social support and the pressure of social exclusion might aggravate family caregiver burden. This study aimed to examine the association between caring load and family caregivers’ burden, as well as the mediating effects of social support and social exclusion. Methods Data used in this study was derived from the nationally representative database of the aged population in China, and 3,125 households with disabled old adults and their home-bound caregivers were eventually selected for this analysis. Regression methods and mediation analysis methods were employed in this study. Results The results indicated that there was a significant positive association between caring load and the caregiver burden, and specifically, social support intensity (rather than social support breadth) and passive social exclusion (rather than active social exclusion) played partial mediating effects. Furthermore, the contributions of mediating effects of social support intensity and passive social exclusion were 13–15 and 27–29%, respectively, and the total contribution of mediating effects was about 35–38%. Conclusion Family caregivers’ burden should be paid more attention to in the large population with rapidly aging speed like China, and more guidance services as well as support should be provided to family caregivers. In addition, it is crucial to focus on the community’s social support and social exclusion in public policy innovation.